Government Failure. Society, Markets and Rules (excerpts) - Wilfred Dolfsma; Юрий Каптуревский; Денис Кадочников (Journal of Economic Sociology, 2017)
This book is devoted to government failures, which imply that the government cannot fulfil its key obligations related to formulating rules. Representing the interests of society, the government establishes rules as frameworks within which market actors should act. However, while market failures have been discussed intensively in the economic literature, government failures are often neglected by scholars. In this book, the author tries to fill this gap through detailed consideration of the meanings of and reasons for government failures. The Journal of Economic Sociology publishes the first chapter, “Introducing Government Failure”, and the second chapter, “How Market and Society Relate”. In the first chapter, the author formulates the research problem and describes the structure of the book. The second chapter investigates how market and society are interrelated from three theoretical perspectives, as follows: society and markets as separate entities, markets embedded in society, and society within the market. The author also explores how markets and governments may contribute to social welfare. The case of healthcare reforms is used for this purpose.